Examine the Risk Factors for Contrast-Induced Nephropathy in Patients Undergoing Percutaneous Coronary Intervention (PCI) and the Prevalence of this Complication - Gauhar Rahman, Hibba Aziz, Naveed Yaqoob, Rifat Yasmin, Mujeebullah Tareen, Faizan Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to determine the incidence of contrast-induced nephropathy and risk variables among patients undergoing multi-vessel percutaneous coronary intervention (PCI). Study Design: Prospective / Observational study Place and Duration: Department of Interventional Cardiology, Peshawar Institute of Cardiology Peshawar in the duration from November 2022 to April, 2023. Methods: There were 168 patients of both genders with ages 20-70 years were presented in this study. Data on enrolled patients' age, gender, BMI, marital status and education level were collected after receiving written permission from each patient. This research included people who had undergone a percutaneous coronary intervention. Serum creatinine >0.5mg/dl from the baseline value was classified as contrast induced nephropathy. CIN-related risk factors were studied. Data was analyzed using SPSS 22.0. Results: Patients mean age was 49.8±19.44 years and with mean body mass index 24.1±7.37 kg/m2. 90 patients were males. CIN was found in 42 (25%) cases. Contrast volume, hypertension, diabetes mellitus, and age >60 were the most common risk factors for CIN. Conclusion: Contrast-induced nephropathy is a serious danger for patients undergoing PCI. Anemia (age >60), diabetes mellitus (contrast volume >150 ml), and heart failure were found to increase the likelihood of developing CIN. Keywords: Contrast Induced Nephropathy, Percutaneous Coronary Intervention, Risk Factors